Tracing the origins of extracellular DNA in bacterial biofilms: story of death and predation to community benefit. Issue 9 (25th November 2021) - Campoccia, Davide; Montanaro, Lucio; Arciola, Carla Renata
Abstract: Extracellular DNA (eDNA) is a macromolecule copiously found in various natural microenvironments, but its origin and significance still remain partly mysterious phenomena. Here, the multifaceted origins of eDNA in bacterial biofilms are explored. The release of eDNA can follow a suicidal programmed bacterial apoptosis or a fratricide-induced death, under the control of quorum sensing systems or triggered by specific stressors. eDNA can be released into the extracellular space or as a free macromolecule or enclosed within membrane vesicles or even through an explosion of bubbles. eDNA can also be derived from host tissue cells through bacterial cytolytic/proapoptotic toxins or stolen from neutrophil extracellular traps (NETs). eDNA can alternatively be produced by lysis-independent mechanisms. Sub-inhibitory doses of antibiotics, by killing a fraction of bacteria, result in stimulating the release of eDNA. Even phages appear to play a role in favoring eDNA release. Unveiling the origins of eDNA is critical to correctly address biofilm-associated infections.